Prospective Use of 1-Aminocyclopropane-1-Carboxylate Deaminase-Producing Bacteria for Plant Growth Promotion and Defense against Biotic and Abiotic Stresses in Peat-Soil-Agriculture - EDI HUSEN; ARIS TRI WAHYUDI; ANTONIUS SUWANTO; RASTI SARASWATI (Microbiology Indonesia, 2008)
The 1-aminocyclopropane-1-carboxylate (ACC) deaminase (EC4.1.99.4) is an enzyme produced by some soil bacteria to degrade ACC (the immediate precursor of ethylene) to reduce ethylene biosynthesis in higher plants. Increased concentrations of ethylene in plant tissues, which are triggered by various biotic and abiotic stresses, inhibits plant growth and weakens the plant defense against the stressors. Various findings on the successful use of ACC deaminase producing bacteria for plant growth under unfavorable soil conditions are inspiring their use in tropical peat-soil-agriculture, which possesses bio-physical constraints. It has been proven that inoculation of plants with ACC deaminase producing bacteria decreased ethylene inhibition generated by unfavorable environmental conditions, such as nutrient shortage, flooding, drought, high salts, and the presence of heavy metals and organic pollutants. Understanding the mechanisms by which ACC deaminase-producing bacteria act to reduce plant stress and the fitness of bacterial traits with the properties and constraints of peat-soils becomes a key to utilize these bacteria in improving crop productivity. The bacteria may ameliorate plant stress as well as promote plant growth under seasonal bio-physical changes of peat-soils that are usually encountered in the field.